(untitled) (Journal of Economic Research & Business Administration, 2024)
The purpose of this study is to identify trends and specifics of the level of poverty in Kazakhstan and give recommendations for reducing its level. The relevance of the study is due to the development of poverty in Kazakhstan, the poor standard of living of the population in the regions, and the lack of food supply for a living. That is, it is ensured by the need to study the problems that caused the growth of the level of poverty in the regions of the state, and the importance of measures to reduce its level. The study raises questions about the factors affecting the increase in poverty. According to the results of the literary review, it was found that the fight against poverty in the world economy is a constantly pressing problem. This study used complex methods such as systematization and grouping of statistical data. Statistics were taken from the National Bureau of statistics for 2018-2022. The developed methodological tools allow us to identify and analyze the situation of determinants that affect the increase in the level of poverty in the regions. According to the results of the study, the factors affecting the level of poverty were the share and number of the population with incomes below the subsistence level (poverty level), the number of people with incomes below the cost of the food basket, the share and number of the unemployed population. It was determined that the regions with a high population with incomes below the subsistence level include Turkestan, Mangistau regions and Almaty, and the regions with low poverty level include Astana and Ulytau region. The theoretical significance of the study can serve as a basis for discussing the level of poverty in the regions and can be used in educational materials. The practical significance of the research results can be used in the preparation of State targeted programs. Key words: economy, poverty, region, analysis, income, unemployment.